2005
DOI: 10.1080/09064700500393532
|View full text |Cite
|
Sign up to set email alerts
|

Production of dairy cows fed whole-crop cereals or ryegrass silages supplemented with a fixed amount of concentrate

Abstract: Feed intake and milk production responses to whole-crop cereal silages and ryegrass silage (RGS) supplemented with a fixed amount of concentrate were measured in three 4)/4 Latin square-designed experiment with three 17-day periods using 12 Holstein cows. Diets consisted of a fixed amount of concentrate (10 kg) and one of the following silages offered ad libitum : RGS, Mondego wheat silage (MWS), Alva wheat silage (AWS), and triticale silage (TS). Silage dry matter intake and milk yield were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The superiority of the Italian ryegrass diet is even more noteworthy since the control diet was superior in regard to energy and protein content and therefore should have promoted higher intakes 21. Previous studies under conventional agriculture conditions associated with high proportions of concentrates (45% of total diet DM) have shown higher intakes of Italian ryegrass silage as compared with corn silage and whole‐crop cereal silages 2, 3. When concentrates were increased to 55% of the total diet DM, no difference in forage intake between Italian ryegrass silage and whole‐crop wheat silage was observed 4…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The superiority of the Italian ryegrass diet is even more noteworthy since the control diet was superior in regard to energy and protein content and therefore should have promoted higher intakes 21. Previous studies under conventional agriculture conditions associated with high proportions of concentrates (45% of total diet DM) have shown higher intakes of Italian ryegrass silage as compared with corn silage and whole‐crop cereal silages 2, 3. When concentrates were increased to 55% of the total diet DM, no difference in forage intake between Italian ryegrass silage and whole‐crop wheat silage was observed 4…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, van Dorland et al 28 observed lower proportions of short‐chain SFA and higher proportions of MUFA in milk fat from cows fed grass silage in comparison with grass/clover silages (red and white clover). When comparing Italian ryegrass silage and whole‐crop cereal silages, Cabrita et al 3 recorded higher levels of short‐chain SFA for the Italian ryegrass treatment but also higher proportions of the unsaturated long‐chain fatty acids C18:2 and C18:3. The n‐6/n‐3 fatty acid ratio in treatment RG was significantly higher than in treatment C. Nevertheless, with ratios below 2:1, milk fat from all cows was well below the recommendation of 5:1 given by DACH29 for human nutrition.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The relatively high digestibility associated with the higher protein content of the studied lupin species than ryegrass and winter-cereal silages [ 59 , 60 ] makes them interesting forages to be used as sustainable protein sources in diets for ruminant animals, including for high-producing animals, namely, in diets based on maize silage for dairy cows. This assumes particular importance in the current context of Europe's high dependence on protein sources, making it highly vulnerable to the international market, and is in line with the measures that have sought to support European protein crops to address the imbalance between supply and demand for plant proteins [ 1 ].…”
Section: Discussionmentioning
confidence: 99%